Antihyperalgesic effects of ProTx-II, a Nav1.7 antagonist, and A803467, a Nav1.8 antagonist, in diabetic mice - Tanaka KI; Sekino S; Ikegami M; Ikeda H; Kamei J (Dove Medical Press, 2015)
Ken-ichiro Tanaka,1,2, Shota Sekino,1 Megumi Ikegami,1 Hiroko Ikeda,1 Junzo Kamei11Department of Pathophysiology and Therapeutics, School of Pharmacy and Pharmaceutical Sciences, Hoshi University, Tokyo, Japan; 2Department of Endocrinology and Metabolism, Graduate School of Medicine, Yokohama City University, Yokohama, JapanAbstract: The present study investigated the effects of intrathecal administration of ProTx-II (tarantula venom peptide) and A803467 (5-[4-chloro-phenyl]-furan-2-carboxylic acid [3,5-dimethoxy-phenyl]-amide), selective Nav1.7 and Nav1.8 antagonists, respectively, on thermal hyperalgesia in a painful diabetic neuropathy model of mice. Intrathecal administration of ProTx-II at doses from 0.04 to 4 ng to diabetic mice dose-dependently and significantly increased the tail-flick latency. Intrathecal administration of A803467 at doses from 10 to 100 ng to diabetic mice also dose-dependently and significantly increased the tail-flick latency. However, intrathecal administration of either ProTx-II (4 ng) or A803467 (100 ng) had no effect on the tail-flick latency in nondiabetic mice. The expression of either the Nav1.7 or Nav1.8 sodium channel protein in the dorsal root ganglion in diabetic mice was not different from that in nondiabetic mice. The present results suggest that ProTx-II and A803467, highly selective blockers of Nav1.7 and Nav1.8 sodium channels, respectively, in the spinal cord, can have antihyperalgesic effects in diabetic mice.Keywords: painful diabetic neuropathy, Nav1.7, Nav1.8, ProTx-II, A803467